2020
DOI: 10.3390/pr8111346
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ferroelastic Creep Behavior of Porous (La0.6Sr0.4)0.95Co0.2Fe0.8O3-δ

Abstract: The time-dependent deformation of porous (La0.6Sr0.4)0.95Co0.2Fe0.8O3-δ (LSCF) under constant uniaxial compressive stress at room temperature has been studied. Both axial and lateral stress–strain deformation curves clearly show the non-linear ferroelastic behavior of LSCF perovskite during compression. The ferroelastic characteristics of deformation curves such as coercive stress and apparent loading moduli decrease when the porosity of the samples increases. Ferroelastic creep deformations at applied stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this equation, two creep parameters, the characteristic time τ and the equilibrium strain increment normalΔϵeq, were used to describe the creep strain at room temperature. Slightly modified Prony series’ empirical equations were used to describe room temperature uniaxial ferroelastic creep in [16,21], however, their approach required a number of empirical parameters to fit experimental time-dependent deformation behaviour of La 0.58 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ based perovskites. The high-temperature non-ferroelastic creep strain was detected in LaCoO 3 in four-point bending testing in [22], however, no detailed analysis of high temperature time dependent phenomenon in LaCoO 3 was performed at that time.…”
Section: Calculation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In this equation, two creep parameters, the characteristic time τ and the equilibrium strain increment normalΔϵeq, were used to describe the creep strain at room temperature. Slightly modified Prony series’ empirical equations were used to describe room temperature uniaxial ferroelastic creep in [16,21], however, their approach required a number of empirical parameters to fit experimental time-dependent deformation behaviour of La 0.58 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ based perovskites. The high-temperature non-ferroelastic creep strain was detected in LaCoO 3 in four-point bending testing in [22], however, no detailed analysis of high temperature time dependent phenomenon in LaCoO 3 was performed at that time.…”
Section: Calculation Proceduresmentioning
confidence: 99%
“…It was reported that these materials, such as LaCoO 3 , LaFeO 3 , LaMnO 3 or LaCrO 3 based perovskites, are ferroelastic and hysteretic upon mechanical loading due to the mobility of their defects, such as domain walls, stacking faults, multiple point defects among others [5][6][7][8][9][10][11][12]. Such defect mobility upon application of stress results in time-dependent continuous deformation that easily occurs in these perovskites even at room temperature [13][14][15][16]. Such room temperature ferroelastic creep is distinctly different from non-ferroelastic creep that mainly occurs in materials at high temperatures due to grain sliding, dislocation movements or even diffusion of atoms upon applied stress [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation